The Phenomenon of Meaninglessness in the Poem “Sawt Safīr al-Bulbul” by Al-Asma‘i: A Reading in Non-functional Aestheticism - ‘Abbās al-Ma‘mūrī, Helen Fāḍil (Journal of Tikrit University for Humanities, 2025)
This study offers a comprehensive aesthetic analysis of the poem “Sawt Safīr al-Bulbul”, through the lens of “non-functional aesthetics”. The poem is examined as a deliberate poetic experiment that rejects semantic coherence and embraces sonic performance, structural absurdity, rhythmic fragmentation, and lexical play. Across four analytical chapters, the study reveals that the poem deconstructs classical poetic conventions, turning language into a performative body rather than a semantic vessel. Ultimately, it argues that this “nonsense” is not a deficiency, but rather a conscious aesthetic resistance, offering an alternative mode of poetic production within Arabic literary culture.